Les atlas des paysages de Wallonie - Thaïs Pons; Marie-Françoise Godart; Mireille Deconinck (Projets de Paysage)
In response to the European convention on landscapes, the region of Wallonia in Belgium has started to characterize its landscapes by producing a collection of atlases that will cover the whole region in the end. This article explains in general how these atlases were elaborated. In addition to the general methodology, which provides a multidisciplinary approach, focus is set on the perception of landscapes by the local stakeholders. Besides its general multi-disciplinary approach, the uniqueness of the method used, is its focus on the perception of landscapes by the stakeholders involved. As a result, the study reveals that a landscape is appreciated not only by its physical appearance but by the combination of physical, emotional and social aspects. The confrontation between the objective landscape analysis and the subjective view of the stakeholders involved proves that these landscape atlases are a means for dialogue between landscape planners and its users.